A Simple Python Testbed for Federated Learning Algorithms - Popovic, Miroslav; Popovic, Marko; Kastelan, Ivan; Djukic, Miodrag; Ghilezan, Silvia (2023 Zooming Innovation in Consumer Technologies Conference (ZINC), 2023)
Nowadays many researchers are developing various distributed and decentralized frameworks for federated learning algorithms. However, development of such a framework targeting smart Internet of Things in edge systems is still an open challenge. In this paper, we present our solution to that challenge called Python Testbed for Federated Learning Algorithms. The solution is written in pure Python, and it supports both centralized and decentralized algorithms. The usage of the presented solution is both validated and illustrated by three simple algorithm examples.